The larva of Rhyacophila palmeni McLachlan 1879 (Trichoptera: Rhyacophilidae) from Greece and Kosovo with notes on ecology and zoogeography including a key to the known Greek Rhyacophila larvae - Karaouzas, Ioannis; Ibrahimi, Halil; Waringer, Johann (Zootaxa, 2018)
The larva of Rhyacophila palmeni McLachlan 1879 is described, based on material from Greece and Kosovo. The diagnostic features of the species are discussed and illustrated, and some information on its ecology and distribution are included. In addition, diagnostic characters for larvae of the known Greek Rhyacophila species are provided.